Analysis of the Icelandic, Irish and Cypriot financial crises - Calleja, Nigel (University of Malta, 2016)
B.COM.(HONS)BANK.&FIN. Financial crises leave a negative impact on economies and the financial sector. When a huge financial crisis hits, normally it results in many other countries being affected as well due to spill over affects. When the Great Financial Crisis hit in 2008 in the US, it spread over to the EU where many countries were also put in stressful economics periods. Three of these countries are going to be discussed in this dissertation; which are Iceland, Ireland and Cyprus. To further understand why the financial crisis occurred, first an analysis of how the economy was doing before the crisis collapsed is done. Afterwards the story of how the crisis started is documented. To enhance the understanding of the effects of the crisis, a look at the economics figures of each case is done and also a look on the effects on the financial sector. Next is determining what was done by the respective authorities to counteract the negative effects of the crisis and what was done to encourage confidence in the public again. Finally, perhaps the most important aspect is what were the lessons learnt from these financial crises as to prevent from such events from happening again. N/A